Retention and motivation of health workers in remote and rural areas in Cross River State, Nigeria: a discrete choice experiment. (13th April 2021) - Okoroafor, S C; Ongom, M; Salihu, D; Mohammed, B; Ahmat, A; Osubor, M; Nyoni, J; Nwachukwu, C; Bassey, J; Alemu, W
ABSTRACT: Background: Cross River State is making investments geared towards ensuring equitable distribution and improved retention of its frontline health workforce in remote and rural areas. This informed the conduct of a discrete choice experiment to determine the motivating factors supporting the retention of healthcare workers. Methods: Study participants were 198 final year students of nursing, midwifery and community health and frontline health workers. Eight focus group discussions and 38 key informant interviews were conducted to obtain information about the dimensions of the work conditions that are important to frontline health workers when choosing to take up posting or stay in their rural work locations. Results: Health workers are 2.7 times more likely to take up a rural posting or continue to stay in their present rural duty posts if they receive a salary increment. They are also four times more likely to take a rural job posting if a basic housing or a housing allowance is provided. Conclusion: Improving working conditions of frontline health workers in terms of adequate staff strength, good skills mix and equipment, etc., as well as improving opportunities for career advancement will support retention in rural health posts.